Introduction to the dossier "Psychoanalysis and autism" - Piro, María Cristina (Facultad de Psicología (Universidad Nacional de La Plata, Argentina), 2021)
Prof. Esp. María Cristina Piro, coordinator of the "Psychoanalysis and autism" dossier, presents its contents.